Effect of Seed Size on Germination and Seedling Performance during Storage of Neem (Azadirachta indica A. Juss) Seeds - Kumar, Devendra (Indian Forester, 2007)
The present study was conducted to determine the effect of various grades of Neem seed’s on germination and seedlings performance during storage. Freshly collected seeds were grouped into three sub-lots viz. larger seeds (size 8 mm or >8 mm), medium seeds (size <8 mm and >6 mm) and small seeds (size <6 mm). Seeds of all grades were sown in nursery beds as fresh and after 35 days of storage. Various grades of seeds had no effect on germination percentage as fresh and after 35 days of storage. Larger size fresh seeds showed significantly higher MGT as compared to medium and small size seeds. Small size seeds showed maximum number of leaves, vigour index, maximum volume index and minimum sturdiness quotient followed by medium and larger size seeds. Significant reduction was observed not only in larger size seeds but also in medium and small size seed with respect to all the seed and seedling parameters during the storage. Stored seeds did not show any significant difference in germination percentage, GV and MGT. Small size seeds showed significantly maximum number of leaves and total biomass followed by medium and larger size seeds after 35 days of storage. Small and medium seeds showed higher volume index, quality index and minimum sturdiness quotient after 35 days of storage. Vigour index showed significant reduction during storage as compared to fresh seeds in all type of seeds. Small and medium size seeds showed significantly maximum vigour index followed by larger size seeds after 35 days of storage. These findings suggest that any grade of fresh neem seed can be sown. If sowing is slightly delayed then small and medium size seeds may be preferred for sowing to get better seed and seedling performance.